2016
DOI: 10.1002/anie.201602936
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR Spectroscopy as a Highly Sensitive Method for the Direct Monitoring of Confined Crystallization within Nanoporous Materials

Abstract: The introduction of fluorine into the structure of pharmaceuticals has been an effective strategy for tuning their pharmacodynamic properties, with more than 40 new drugs entering the market in the last 15 years. In this context, (19) F NMR spectroscopy can be viewed as a useful method for investigating the host-guest chemistry of pharmaceuticals in nanosized drug-delivery systems. Although the interest in confined crystallization, nanosized devices, and porous catalysts is gradually increasing, understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…About 25 % of all marketed drugs are fluorinated molecules and developing novel nano-confined pharmaceutical formulations as drug delivery systems can have day-to-day applications. Nartowski et al 363 Azaïs et al have applied DFT calculations and ssNMR spectroscopy to determine the origin and the strength of the interactions at the molecular level for Ibuprofen and benzoic acid, encapsulated in hydrated MCM-41 modified with organic moieties. 364 They have observed both by calculations and experimental methods that micro-solvated silica surface was found to adsorb better Ibuprofen and benzoic acid than the bare silica surface at 300 K. The water layer acted as an adhesive between the organic molecules and the silica surface, where rapid reorientation of the molecules inside the mesoporous silica occur due to adsorption/desorption induced by the interactions.…”
Section: Mesoporous Solids For Drug Deliverymentioning
confidence: 99%
“…About 25 % of all marketed drugs are fluorinated molecules and developing novel nano-confined pharmaceutical formulations as drug delivery systems can have day-to-day applications. Nartowski et al 363 Azaïs et al have applied DFT calculations and ssNMR spectroscopy to determine the origin and the strength of the interactions at the molecular level for Ibuprofen and benzoic acid, encapsulated in hydrated MCM-41 modified with organic moieties. 364 They have observed both by calculations and experimental methods that micro-solvated silica surface was found to adsorb better Ibuprofen and benzoic acid than the bare silica surface at 300 K. The water layer acted as an adhesive between the organic molecules and the silica surface, where rapid reorientation of the molecules inside the mesoporous silica occur due to adsorption/desorption induced by the interactions.…”
Section: Mesoporous Solids For Drug Deliverymentioning
confidence: 99%
“…Nuclear magnetic resonance is one of few useful techniques to directly probe the molecular order and structure of constituent molecules in liquid crystals . Recently, Nartowski et al demonstrated that 19 F NMR is a powerful tool to investigate the order of molecular guests confined inside of mesoporous silica materials . To get insight into the dynamics of the alignment of the liquid crystalline HBAs inside the mesoporous materials, variable‐temperature solid‐state 19 F NMR studies of the composites were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Change in scattering contrast was witnessed between unloaded and loaded samples, with the principal peak within the loaded diffraction pattern displaying a broader nature with a lower intensity [39]. In a study by Nartowski and collaborators, 19 F solid-state NMR together with terahertz spectroscopy was used to detect the presence of confined molecules of flufenamic acid (FFA) in different environments and motional regimes [40]. This enabled the authors to gain in situ mechanistic insight into the molecular self-assembly at different length scales by taking advantage of the higher sensitivity of 19 F nuclei to changes in the local environments of molecules confined in the porous hosts.…”
Section: Crystallisation Characterisation Techniquesmentioning
confidence: 99%